Mentalos: um card game para ajudar na concentração de pacientes com TDAH - Giampaulo, Daniel Minoh (2021)
This research has as general objective an analogue game for the medical area within the area of psychiatry, contemplating its main fundamentals and elements of card games, and its development process based on a game of mysteries and riddles. What justifies this investigation is the scarcity of debate on the proposed theme, from the point of view of the development of games for health, it presents a lack of playful games in the health area when compared to other areas of the games industry, especially in Brazil. What motivates this research is the possibility of investigating alternatives that can contribute to the evolution of the serious game development industry in Brazil, with no sense of incentive for the development of an educational game product currently used for training, and that can be exploited using psychiatric care centers. This investigation seeks to answer the following question: how to develop focused analog games for patients diagnosed with ADHD? It is considered the hypothesis that physical analog games, through its old technology, is feasible for the development of card games in the industry scenario would be digital and analog games. We opted for the qualitative descriptive scientific research methodology, with the origin of bibliographic / documentary data, with place of realization, since it faces theoretical and empirical aspects, in order to fulfill its general objective. A review of previous studies related to the theme focused on the period between 1798 to 2020, including books, scientific articles, theses and dissertations, considering research available in the following online databases:, a) Capes Thesis and Dissertation Bank, b) SBGames - Simpósio Brasileira de Games, c) Google Scholar. The articles available in Scientific Electronic Library Online – SciELO,d) SBEI - Simpósio Brasileiro de Informática na Educação from the scientific journals classified as level A1 to A3 of Qualis-Capes in the area of interdisciplinary and medicine, were also considered for a review of previous studies. The instruments of data collection will be practical executions, discovery and observation. The theoretical references that support this investigation are the concepts of board games (BELL, 1960);, games in the medical field (VASCONSELLOS, 2018), (CARVALHO, 2018), (ARAÚJO, 2018). The context of this investigation involves spaces for research, teaching and extension of the institutions where research partners work. The expected results with this research are: 1) Development of a card game for ADHD taking as a reference the previous studies and theoretical references addressed; 2) The product can be used in the near future